A Comparative Study of The Etymologies of Isidore of Seville and the Shuowen Jiezi of Xu Shen - Ziwei, Wang; Jinjing, Xu (Sinología hispánica. China Studies Review, 2026)
Etymologies (by Isidore of Seville, Spain,7th century A.D. is the earliest etymological dictionaries in the Eastern world and which is the most important basic teaching material in Spanish educational systems. Similarly, Shuowen Jiezi, which was finished by Xu Shen in the Han dynasty, has paralleling significance in Chinese traditional culture. Both of the two dictionaries were born in a similar context, which was the beginning of a new era after the devastation of ancient civilizations. The authors of the two books were both the most erudite scholars at the time and the country they lived in. Both of them had been focusing on etymologically tracing and organizing classical knowledge. If we compare the background, main ideas, style, content, and characteristics of both, as well as their cultural differences and similarities (including values, gender notions, social roles, context, symbolic meanings, and shared perspectives), we will be able to gain a deeper understanding of the relationship between Eastern and Western civilizations. This historical and cultural perspective will not only help us better understand the development of human civilization, but it can also provide new insights for cross-cultural and second language teaching.